Vaccine-induced thrombosis and thrombocytopenia (VITT) in Ireland: A review of cases and current practices - D. Swan (Elsevier, 2021)
Since the beginning of the Severe Acute Respiratory Syndrome Coronavirus-2 (SARS CoV-2) virus pandemic, several highly effective and safe vaccines have been produced at remarkable speed. Following global implementation of vaccination programmes, cases of thrombosis with thrombocytopenia following administration of adenoviral vector-based vaccines started being reported.In this review we discuss the known pathogenesis and epidemiology of so-called vaccine induced thrombocytopenia and thrombosis (VITT). We consider the available guidelines, diagnostic laboratory tests and management options for these patients. Finally, we discuss important unanswered questions and areas for future research in this novel pathoclinical entity.